International entrepreneurial alertness in opportunity discovery for market entry. Issue 2 (16th December 2019) - Rezvani, Mehran; Lashgari, Mahdi; Yadolahi Farsi, Jahangir
Abstract : Purpose: The purpose of this study is to change the level of entrepreneurial alertness from individual to group and from the group to the organizational level and apply it to international market entry. Design/methodology/approach: A literature review, meth-synthesis, interview and focal group are used for the final research framework. The way of theorizing for changing levels of entrepreneurial alertness is multi-level method. A framework for international market entry, a process of internationalization and an organizational learning process was used for the final conceptual framework. Findings: A new framework for international entrepreneurial alertness in the opportunity discovery of individual, group and organizational level was developed. Research limitations/implications: Researchers will be able to use this framework for extending opportunity discovery and entrepreneurial alertness theories at individual, group, organizational and international levels. Practical implications: Using the final framework, entrepreneurs and organizations will be able to discover new opportunities, and teachers will be able to educate international entrepreneurial alertness and opportunity discovery at individual, group and organizational levels. Originality/value: The paper begins with an overview of previous researches in this area and then moves on to combine them using meth-synthesis to create a new framework for international entrepreneurial alertness in opportunity discovery. Note that the levels of entrepreneurial alertness from individual to group and from the group to the organizational level have been changed using a multi-level theorizing method.